Organosulfonic acid functionalized zeolite ZSM-5 as temperature tolerant proton conducting material - Nur H.; Kee G.L.; Hamdan H.; Indra Mahlia T.M.; Efendi J.; Cornelis Metselaar H.S. (2023)
Organosulfonic acid functionalized zeolite ZSM-5 materials namely sulfonated polystyrene ZSM-5, phenylsulfonic acid functionalized ZSM-5 and propylsulfonic acid functionalized ZSM-5, were successfully synthesized in this study. Characterization by X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectrometers indicate that the functionalized zeolites comprise of the organosulfonic acid groups attached onto the surface of zeolites. Impedance spectroscopy results showed that the proton conductivities of zeolites in the operating temperature range of 24-100C were enhanced significantly to higher values (about 1-3 orders of magnitude) by loading of sulfonic acids onto the surface of zeolite. Proton conductivities were correlated with the concentration of sulfonic acid groups and increased as follows: sulfonated polystyrene ZSM-5 > phenylsulfonic acid functionalized ZSM-5 > propylsulfonic acid functionalized ZSM-5 which is in line with the ion-exchange capacity, acidity and water uptake analysis. The high proton conductivity of sulfonated polystyrene ZSM-5 might be explained by using surface diffusion mechanism. 2012 Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.